PELAKSANAAN PEMUTUSAN HUBUNGAN KERJA SECARA LISAN TERHADAP PEKERJA DI CV. LIMS KOKTONG PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Tampubolon, Kristin; Lestari, Rika; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Termination of employment is very detrimental to the worker because it will not only affect the loss of permanent employment of the worker but also the loss of the main source of the livelihood of the workers and their families. And often the termination of employment by employers does not follow the procedures and provisions of the Manpower Act to the detriment of workers rights. The purpose of writing this thesis, namely: First, to determine the implementation of termination of work done orally against workers in the CV. Lims Koktong under Act No. 13 of 2003 on employment. Second, to know the legal protection against workers who were laid off verbally in the CV. Lims Koktong Pekanbaru.This type of research can be classified in the type of sociological juridical research because in this study researchers directly conduct research in the location or place studied in order to provide a complete picture of the problem under study. This research was conducted at CV. Lims Koktong Pekanbaru. While the population and sample are all parties related to the problem under study. In this study the data source used is primary data, secondary data, and tertiary data. Data collection techniques were conducted by observation, interview and literature study.From the results of research problems there are two main things that can be concluded. Firstly, the company has committed a violation related to the termination of employment which is done orally and not in accordance with the procedure of the layoffs which have been stipulated in the provisions of Law Number 13 Year 2003 on Manpower set forth in Article 151,152,154,156. Second, the termination of employment which has been done by the company has caused loss to the workers and the rights of the worker have been protected by law and should be given by the entrepreneur when dismissing the employment. Suggestion of the writer, Firstly, Should if the company wishing to terminate the employment of its workers should be guided by the established procedure and following all the provisions and procedures set forth in Law Number 13 Year 2003 on Manpower. Secondly, if the company wishes to terminate the employment should grant the employees laid-off rights.Keywords: Termination of Employment, Legal Protection, Workers / Laborers.